Analysis of mediastinal lesions: a study of 27 cases - S Karki; S Chalise (Association of Clinical Pathologists of Nepal, 2011)
Background: Mediastinum is a site of non-neoplastic and neoplastic lesions, many of which present as mediastinal masses. The purpose of this study was to study our institutional experience of mediastinal lesions on fine needle aspiration cytology or biopsy. Materials and Methods: This was a retrospective study of 27 patients, who had undergone fine needle aspiration cytology or biopsy for mediastinal lesions from April 2009 to November 2010 in the Department of Pathology, Institute of Medicine, Tribhuwan University Teaching Hospital. All details of the patients pertinent clinical history was obtained from case record file in the department. Results: Out of 27 cases, 18 cases (66.6%) were benign and 7 (26%) were malignant and 2 (7.4%) were inconclusive. Among the malignant lesions, primary tumors constituted 71.5% of cases while metastases were 28.5%. Most of the lesions were seen in the anterior compartment followed by the posterior compartment. Age range was 4 months to 70 years with a mean age of 35.5 years. Thymoma (8 cases) was the commonest lesion seen in mediastinum followed by germ cell tumor and neurogenic tumor. Conclusion: Benign mediastinal lesions are more common than malignant lesions with thymoma being the most commonly diagnosed mediastinal lesion. Keywords: Mediastinum; Germ cell tumor; Thymoma; Non Hodgkin Lymphoma DOI: http://dx.doi.org/10.3126/jpn.v1i2.5404 JPN 2011; 1(2): 114-117